The Necessity and Prospects for the Development of the Life Insurance Market in Uzbekistan - Kiyasov, Sherzod Uralovich (Yayasan Sinergi Kawula Muda, 2025)
This article analyzes the possibilities of ensuring financial protection of the population and attracting long-term investments through the popularization of life insurance. The article also proposes introducing new technologies for life insurance services and developing modern sales instruments. The study studies foreign experiences and analyzes the possibilities of applying these experiences to the conditions of Uzbekistan. The authors, focusing on the social and economic importance of life insurance, substantiate the relevance of digitalization and the introduction of innovative solutions for the development of the industry. At the same time, the article presents recommendations for improving modern insurance marketing strategies and customer service standards.